2019
DOI: 10.1038/s41524-019-0189-9
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learned multi-system surrogate models for materials prediction

Abstract: Surrogate machine-learning models are transforming computational materials science by predicting properties of materials with the accuracy of ab initio methods at a fraction of the computational cost. We demonstrate surrogate models that simultaneously interpolate energies of different materials on a dataset of 10 binary alloys (AgCu, AlFe, AlMg, AlNi, AlTi, CoNi, CuFe, CuNi, FeV, NbNi) with 10 different species and all possible fcc, bcc and hcp structures up to 8 atoms in the unit cell, 15 950 structures in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 51 publications
3
81
0
Order By: Relevance
“…(3)); the resulting quantity we refer to as the mean absolute error, MAE) of 14.2, 14.1, and 14.7 meV/cation, respectively. This confirms previously reported virtually indistinguishable accuracies for MBTR and SOAP in the prediction of formation energies of alloys 40 . However, using the proposed method, key differences can be observed in the MAEs of their respective DAs (see Table 2 and Fig.…”
Section: Domain Of Applicability Identification Via Subgroup Discoverysupporting
confidence: 93%
“…(3)); the resulting quantity we refer to as the mean absolute error, MAE) of 14.2, 14.1, and 14.7 meV/cation, respectively. This confirms previously reported virtually indistinguishable accuracies for MBTR and SOAP in the prediction of formation energies of alloys 40 . However, using the proposed method, key differences can be observed in the MAEs of their respective DAs (see Table 2 and Fig.…”
Section: Domain Of Applicability Identification Via Subgroup Discoverysupporting
confidence: 93%
“…The training procedure is thus a nonlinear optimization which is solved using the Broyden-Fletcher-Goldfarb-Shanno (BFGS) algorithm. MTPs have been tested on a number of atomic modeling applications [51], where they demonstrate excellent characteristics for reproducing the properties of both single-component [41,52] and multicomponent materials [40,43].…”
Section: Training Of Interatomic Potentialsmentioning
confidence: 99%
“…First, it only needs a relatively simple ML model for the response prediction, based on which the pattern generation can be directly realized, thus the training is not computationally expensive compared with similar studies 30,69,70 . Second, while the architecture of the ML model is not complicated, it is capable of predicting the entire nonlinear response history with plasticity and large deformation other than individual properties 10,18,28 . Third, from the geometric perspective, it is able to predict the response for the majority of the patterns although the ML model alone as a surrogate method run into difficulty to provide accurate response for patterns with a larger infill number.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to recent advances in computational power and robust algorithms, we have witnessed the rise of an interdisciplinary field in computational material science [6][7][8][9] . Specifically, researchers have already shown success in utilizing ML-based or other AI methods in two major categories: (1) to accelerate the prediction of material properties for specific applications [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , and (2) to accelerate the on-demand design and the optimization of material microstructure and composition for targeted properties [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . These promising studies have shown superior effectiveness of ML techniques compared to traditional computational modeling or experimental measurements on a variety of materials.…”
Section: Introductionmentioning
confidence: 99%